Weighting Approaches on Online Sexual Abuse of Children: Cultural Prevention or Crime-Based Enforcement? - Sofian, Ahmad; Pratama, Bambang; Talerico, Chiara (Udayana Journal of Law and Culture; Vol 2 No 2 (2018): Encouraging Cultural Approach to Law, 2018)
Online Child Sexual Exploitation (OCSE) is a form of crime against children that can be reviewed from various perspectives such as criminal law, criminology and culture. This offence is governed in several international legal instruments because perpetrators and victims are often located in different territories or have different nationalities. The Optional Protocol on Sale of Children, Child Prostitution and Child Pornography (OPSC) is one that provides a reference in combating this crime, but this instrument has the disadvantage of not providing specific guidance in overcoming sexual crimes of children who are in the online sphere. OPSC focuses more on child pornography, whereas OCSE has evolved rapidly enough to give birth to new forms of crime that are not just child pornography. Another weakness can be found in national laws, due to the lack, or limited, response to address the issue. Therefore, a cultural approach is important to prevent and tackle this problem. This paper is aimed to weight the needs to use a Preventive Cultural approach and a Crime-Based Enforcement in addressing Online Sexual  Abuse in Indonesia. It is a normative legal research that reads various primary and secondary legal materials. The study recommends that there is a need to use appropriate legal terminology and provide a clear interpretation of the terminology in national law so that these crimes can be quickly addressed. In addition, it also argued that cultural approaches may be used to prevent the occurrence of OSCE by means of involving the community and religious leaders, educating family, as well as raising the awareness of children.